2015
DOI: 10.1007/s00018-015-1965-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of connexins and pannexins in reproductive organs

Abstract: Reproductive organs are complex and well-structured tissues essential to perpetuate the species. In mammals, the male and female reproductive organs vary on their organization, morphology and function. Connectivity between cells in such tissues plays pivotal roles in organogenesis and tissue functions through the regulation of cellular proliferation, migration, differentiation and apoptosis. Connexins and pannexins can be seen as major regulators of these physiological processes. In the present review, we asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 187 publications
0
17
0
Order By: Relevance
“…Small metabolites conveyed through gap junctions but also channel-independent effector functions of the cytosolic C-terminal domain (CT) of Cxs control crucial cell processes, including cell growth, in physiology and disease (Naus and Laird, 2010; Kibschull et al, 2015; Leithe et al, 2018). Tissue ischemia activates a cascade of vasodilatory, inflammatory and remodeling processes and endothelial Cxs are increasingly recognized to orchestrate these events.…”
Section: Discussionmentioning
confidence: 99%
“…Small metabolites conveyed through gap junctions but also channel-independent effector functions of the cytosolic C-terminal domain (CT) of Cxs control crucial cell processes, including cell growth, in physiology and disease (Naus and Laird, 2010; Kibschull et al, 2015; Leithe et al, 2018). Tissue ischemia activates a cascade of vasodilatory, inflammatory and remodeling processes and endothelial Cxs are increasingly recognized to orchestrate these events.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that not only TJ but also GJ are required for adequate functioning of the testis. In adult male, connexin 43 (Cx43), the most abundant testicular GJ protein is predominantly localized at the region of BTB and among Leydig cells within the interstitial tissue [ 5 , 6 ]. Studies on Sertoli cell-specific deletion of Cx43 revealed that this connexin is an absolute requirement for the Sertoli cell development and initiation of spermatogenesis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various types of connexins are expressed in the mammalian female reproductive system, which plays an important role in its physiology. Cx43 and Cx37 are predominantly expressed in the ovarian follicles of humans and mice [12]. In both mice and humans, Cx43 forms gap junctions that connect granulosa cells [13,14].…”
Section: Wwwbjbmsorgmentioning
confidence: 99%
“…In both mice and humans, Cx43 forms gap junctions that connect granulosa cells [ 13 , 14 ]. In mice, Cx37 connects oocytes with the surrounding cumulus cells; while in humans, the location of Cx37 in the granulosa cells of fertile women is not clear [ 12 ]. In the endometrium in both rats and humans, Cx26 and Cx43 are the two major connexins [ 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%